Insight into the photoinduced phenomena in ternary Ge-Sb-Se sputtered thin films - Halenkovič, Tomáš; Kotrla, Magdaléna; Gutwirth, Jan; Nazabal, Virginie; Němec, Petr (Chinese Laser Press, 2022)
The kinetics of photoinduced changes, namely, photobleaching and photodarkening in sputtered ternary Ge29Sb8Se63 thin films, was studied. The study of time evolution of the absorption coefficient Delta alpha(t) upon roomtemperature near-bandgap irradiation revealed several types of photoinduced effects. The as-deposited films exhibited a fast photodarkening followed by a dominative photobleaching process. Annealed thin films were found to undergo photodarkening only. The local structure studied by Raman scattering spectroscopy showed significant structural changes upon thermal annealing, which are presumably responsible for a transition from the photobleaching observed in as-deposited and reversible photodarkening in annealed thin films. Moreover, a transient photodarkening process was observed in both as-deposited and annealed thin films. The influence of the initial film thickness and laser optical intensity on the kinetics of photoinduced changes is discussed.
Náhlednutí do světlem indukovaných jevů v ternárních Ge-Sb-Se naprašovaných tenkých vrstvách
Keywords: light; raman; světlo; raman